2020
DOI: 10.1111/andr.12758
|View full text |Cite
|
Sign up to set email alerts
|

Simvastatin alleviated diabetes mellitus‐induced erectile dysfunction in rats by enhancing AMPK pathway‐induced autophagy

Abstract: Background: Diabetes mellitus-induced erectile dysfunction is a common diabetic complication, and new therapeutics and the pathogenesis of diabetes mellitus-induced erectile dysfunction need to be investigated. Objectives:The aim was to investigate the pathogenesis of diabetes mellitus-induced erectile dysfunction and the pharmacological mechanism of simvastatin treatment in diabetes mellitus-induced erectile dysfunction model rats. Materials and methods:A total of 86 male Sprague Dawley rats aged 8 weeks old … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 61 publications
0
13
0
Order By: Relevance
“…Recent studies have shown that simvastatin lead to cell-cycle arrest via AMPK activation and STAT3/SKP2 axis inhibition [ 41 , 74 ]. Ding et al demonstrated that simvastatin could activate the AMPK-SKP2-CARM1 pathway, upregulate protective autophagy, and inhibit corpus cavernosum fibrosis and improved erectile function in diabetes-induced erectile dysfunction rats [ 75 ].…”
Section: Ampk-associated Therapeutic Effects Of Statinsmentioning
confidence: 99%
“…Recent studies have shown that simvastatin lead to cell-cycle arrest via AMPK activation and STAT3/SKP2 axis inhibition [ 41 , 74 ]. Ding et al demonstrated that simvastatin could activate the AMPK-SKP2-CARM1 pathway, upregulate protective autophagy, and inhibit corpus cavernosum fibrosis and improved erectile function in diabetes-induced erectile dysfunction rats [ 75 ].…”
Section: Ampk-associated Therapeutic Effects Of Statinsmentioning
confidence: 99%
“…In the recent few years, the role of autophagy in diseases have been widely explored, including cardiovascular diseases February 2021 | Volume 12 | Article 621132 such as myocardial infarction (Liu et al, 2020;Shi et al, 2020) and atherosclerosis (Wang et al, 2019;Cao et al, 2020), neurodegenerative disorders like multiple sclerosis (Shao et al, 2017;Andhavarapu et al, 2019), metabolic diseases including diabetes (Marasco and Linnemann, 2018;Ding et al, 2020) and obesity (Bartelt and Widenmaier, 2020) and inflammatory and immunerelated disorders such as IBD (Dalmasso et al, 2019;Tan et al, 2019;Sola Tapias et al, 2020), and arthritis (Vomero et al, 2018). Although the inflammatory and immune suppressive effect of autophagy has been revealed, some researchers also identified autophagy as a form of cellular death.…”
Section: Biological Characteristics Of Autophagymentioning
confidence: 99%
“…In a rat model of hyperlipidemia and ED, dietary changes were linked to positive effects on penile hemodynamics [143]. Chronic statin treatment, through its anti-oxidative effects on the endothelium, seems effective in restoring erectile function in diabetic rats [144,145].…”
Section: From CV Risk Identification To Cv Risk Modificationmentioning
confidence: 99%